2016
DOI: 10.14710/jitaa.41.1.37-44
|View full text |Cite
|
Sign up to set email alerts
|

FEEDING EFFECT OF INULIN DERIVED FROM DAHLIA TUBER COMBINED WITH Lactobacillus sp. ON MEAT PROTEIN MASS OF CROSSBRED KAMPONG CHICKEN

Abstract: ABSTRAKPenelitian bertujuan untuk mengevaluasi pengaruh pemberian tepung umbi dahlia yang dikombinasikan dengan Lactobacillus species (Lactobacillus sp.) terhadap aktifitas antioksidan, massa kalsium, dan massa protein pada daging ayam kampung persilangan. Ternak penelitian adalah ayam kampung persilangan umur satu hari unsex sebanyak 168 ekor diberi perlakuan mulai umur 3 minggu. Penelitian menggunakan rancangan acak lengkap pola faktorial 2x3 dengan 4 ulangan. Faktor pertama adalah pemberian dua level tepung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
3
14
0
3
Order By: Relevance
“…The formulation and nutritional contents of basal diet in the present study was completely similar to those reported by Abdurrahman et al (2016) due to the continuation of the study. Diet was formulated with 19% protein and 2800 kcal/kg for starter period and 18% and 2800 kcal/kg for finisher period.…”
Section: Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The formulation and nutritional contents of basal diet in the present study was completely similar to those reported by Abdurrahman et al (2016) due to the continuation of the study. Diet was formulated with 19% protein and 2800 kcal/kg for starter period and 18% and 2800 kcal/kg for finisher period.…”
Section: Methodssupporting
confidence: 87%
“…In connection with the previous studies, it can be assumed that the increased meat protein mass of crossbred local chicken due to the supplementation of prebiotic combined with probiotic followed by the increase in myosin content. Thus, the highest value of lightness breast meat found in D1L2 could be associated with the highest meat protein mass as it was previously reported by Abdurrahman et al (2016).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations